THE MATHEMATICAL MODELING OF THE PROCESS OF NEUTRALIZATION CLOUDS OF HYDROGEN CYANIDE - Lysnyak, V. M. (Science and Transport Progress, 2008)
A computer model to calculate the neutralization of НСN cloud is proposed. The model is based on the numerical integration of the 3-D gradient transport model. The results of numerical experiment are presented.